Implementasi Strategi Komunikasi untuk Meningkatkan Pemanfaatan Website Klampid New Generation Pada Dinas Kependudukan dan Pencatatan Sipil Surabaya - Rahmatia, Alaiki Rizky; Roosinda, Fitria Widiyani; Alfraita, Ariyan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2025)
Although the innovation of digitalization of population administration services has been launched through the Klampid New Generation (KNG) website, the utilization of this platform among the community is still not optimal. This study aims to analyze the implementation of communication strategies used by the Surabaya Population and Civil Registration Service in increasing the utilization of the Klampid New Generation website. This study uses a qualitative descriptive method using Berlo's Communication Model Theory. The results of the study show that the Surabaya Disdukcapil implements a multi-channel communication strategy through social media, official websites, and direct counseling in sub-districts and villages. This strategy is supported by informative and relevant content that is easy for the community to understand. By implementing Berlo's communication theory, each element of communication is optimized, including training of officers in sub-districts to improve understanding of the KNG community.